ANALISIS KEBIJAKAN PENYELENGGARAAN SEKOLAH RAKYAT DALAM TATA KERJA DAN PENERIMAAN PESERTA DIDIK BARU - Fikri Rafsanjani, Mohammad; Mukti, Saepul; Muhamad Kosim, Rijal; Hidayat, Ara; Supiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the policy on the implementation of Sekolah Rakyat focusing on institutional governance and student admission procedures, as regulated in the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 7 of 2025 and the Decree of the Minister of Social Affairs Number 189 of 2025. Sekolah Rakyat is a social-based education policy designed to provide free formal education for children from extremely poor, poor, and vulnerable families as part of Indonesia’s strategy to eradicate extreme poverty. This research employs a qualitative approach using policy analysis research through a literature study (library research). Data were collected from policy documents, laws and regulations, books, and relevant scholarly articles. Data analysis was conducted through policy content analysis and normative analysis to assess the alignment of the policy with the principles of educational equity and social justice. The findings indicate that the institutional governance of Sekolah Rakyat has been normatively regulated in a comprehensive manner, including organizational structure, institutional functions, and cross-sectoral coordination mechanisms. The student admission policy applies principles of affirmation, transparency, and non-discrimination, prioritizing school dropouts and children from extremely poor families. This policy has significant potential to support equitable access to education and to function as a social elevator in breaking the cycle of intergenerational poverty. However, the study also identifies several challenges, including the absence of national education standards for Sekolah Rakyat, potential overlaps of authority among ministries, and the need for sustainable funding and a measurable monitoring system. This study concludes that Sekolah Rakyat represents a progressive and relevant affirmative education policy; nevertheless, strengthening regulatory, operational, and sustainability aspects is essential to ensure its optimal contribution to extreme poverty eradication and educational equity in Indonesia.